2019
DOI: 10.4103/jfmpc.jfmpc_398_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patient characteristics of Helicobacter pylori among adult in primary health care of security forces hospital Riyadh, Saudi Arabia, 2018

Abstract: Aim: To estimate the Helicobacter pylori prevalence and patients’ characteristics in primary health care in security forces hospital Riyadh, Saudi Arabia. Methods: A cross-sectional study, using a fecal H. pylori antigen, is including adults (14-64 years) in the duration from 18 March 2018 to 18 April 2018 on Saudi male and female visiting Primary care center in Security Forces Hospital, Riyadh, Saudi Arabia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Our study indicated high proportion of H. pylori infection in the age groups of 19-32 years and 33-46 years with insignificant difference. This was comparable to different previous studies (Zhu et al, 2014;Chandrababu et al, 2016;Mabeku et al, 2018;Alharbi and Ghoraba, 2019). Contrary to this, other studies reported the average age of infected patients of H. pylori in the age group of 40-49 years (Simón et al, 2016) and 50-59 years (Syam et al, 2015), other studies showed a predictor of H. pylori infection takes place early in childhood (Mabeku et al, 2018;Daniyan et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Our study indicated high proportion of H. pylori infection in the age groups of 19-32 years and 33-46 years with insignificant difference. This was comparable to different previous studies (Zhu et al, 2014;Chandrababu et al, 2016;Mabeku et al, 2018;Alharbi and Ghoraba, 2019). Contrary to this, other studies reported the average age of infected patients of H. pylori in the age group of 40-49 years (Simón et al, 2016) and 50-59 years (Syam et al, 2015), other studies showed a predictor of H. pylori infection takes place early in childhood (Mabeku et al, 2018;Daniyan et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…This study also found a significant association between the item that assessed whether the students had heard about H. pylori, and their knowledge level. Undeniably, H. pylori infection is highly prevalent in developing countries whereas in Saudi Arabia it is hyperendemic [29]. The Ministry of Health in Saudi Arabia has an electronic media interface that publishes information on health issues through the awareness platform, which is accessible to the public, including students.…”
Section: Discussionmentioning
confidence: 99%
“…twitter, WhatsApp.) According to the previous prevalence rate of GERD or heartburn (since dyspepsia prevalence in Saudi Arabia is unknown) of 28.7% ( Alsuwat et al, 2018 ), the sample size (N) was calculated using the following formula: N = z 2 × p × q / d 2 ( Arora et al, 2019 , Alharbi and Ghoraba, 2019 , Alrashed et al, 2019 ); Where: N is the minimum sample size, z is the level of confidence according the normal standard distribution which corresponds to the 95% confidence interval (z = 1.96), p is the prevalence of GERD (0.287), q = (1-p), and d is the desired degree of accuracy or tolerated margin of error which is 5% (0.05). N = (1.96) 2 × 0.29 × (1–0.29) / (0.05) 2 = 314; N = 314 people …”
Section: Methodsmentioning
confidence: 99%